Body Mass Index and Academic Achievement Among Chinese Secondary School Students: The Mediating Effect of Inhibitory Control and the Moderating Effect of Social Support - Shi, Yaohui; Yu, Haibo; Di, Siyu; Ma, Chao (Frontiers in Psychology, 2022)
Based on Embodied Cognition Theory, Inhibitory Decline Theory, and Risk Protective Factors Model, this study verified that BMI affects secondary school students' academic performance through the mechanism of inhibitory control. In addition, it was verified that the strength of this mechanism depends on the teacher, parent, and peer support received by secondary school students. By using height and weight measurements, the classic stroop task, and the social support scale, 264 secondary school students in Shanxi Province, China, were surveyed and their academic performance was collected. The results showed that students with high BMI had poorer academic performance, and inhibitory control partially mediated the effect between BMI and academic performance, with the inhibitory control mediated effect accounting for 36.68% of the total effect. Support from teachers, parents, and peers can ameliorate the negative effects of BMI on academic performance, with teacher support and parental support also ameliorating the negative effects of BMI on inhibitory control. Thus, high BMI impairs inhibitory control and thus has a negative impact on academic performance, which can be buffered by social support.